2016
DOI: 10.1177/0143034316681378
|View full text |Cite
|
Sign up to set email alerts
|

School corporal punishment, family tension, and students’ internalizing problems: Evidence from India

Abstract: There is considerable evidence that parental corporal punishment (CP) is positively associated with children's behavioral and mental health problems. However, there is very little evidence addressing whether CP perpetrated by teachers or school staff is similarly associated with problematic student functioning. To address this gap in the research literature, data were collected from students in a locale where school CP continues to be widely practiced. Participants were 519 adolescents attending public or priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…With the exception of one study, these rates ranged from 60% to 100% of schools studied (Ajowi & Simatwa, 2010; Egwunyenga, 2010; Ekanem & Edet, 2013; Ncontsa & Shumba, 2013; Owusu & Manger, 1996). Of those that measured students’ experiences of corporal punishment in high school, the prevalence rates were still notably high, particularly in the Southeast Asian region where the modal reported rates were 50%–60% (Deb et al, 2017; Raikhy & Kaur, 2009, 2011). Two studies in the Western Pacific region reported similar lifetime rates of corporal punishment for primary students (25%; Ahmed et al, 2015) and high school students (24.3%; Lee, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of one study, these rates ranged from 60% to 100% of schools studied (Ajowi & Simatwa, 2010; Egwunyenga, 2010; Ekanem & Edet, 2013; Ncontsa & Shumba, 2013; Owusu & Manger, 1996). Of those that measured students’ experiences of corporal punishment in high school, the prevalence rates were still notably high, particularly in the Southeast Asian region where the modal reported rates were 50%–60% (Deb et al, 2017; Raikhy & Kaur, 2009, 2011). Two studies in the Western Pacific region reported similar lifetime rates of corporal punishment for primary students (25%; Ahmed et al, 2015) and high school students (24.3%; Lee, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…When considering the first theme of 'punishment', it was identified that East and South Asian countries such as India (Deb, Kumar, Holden, & Simpson Rowe, 2017), Bangladesh (Mohiuddin, Khatun, & Al-Kamal, 2012), Korea, Japan, and Taiwan (Baumann et al, 2020) has a higher level of academic performance due to high levels of discipline in the classrooms.…”
Section: Punishmentmentioning
confidence: 99%
“…The second aim concerns what forms of aggressive behaviors tend to be accepted by teachers and parents: verbal or physical. Previous research has demonstrated the negative impact of aggressive behaviors, both verbal and physical, on students ( Brendgen et al., 2007 ; Deb et al., 2017 ; Fromuth et al., 2015 ; Gershoff, 2017 ; Lee, 2015 ; Longobardi et al., 2018 ; Riley et al., 2010 ). For example, Geiger (2017) showed that teachers' verbal aggressive behavior increased students' aggressive behavior, their tendency to withdraw from class participation, and ignoring their teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study uses the term teachers' aggressive behaviors, it is worth noting that the topic is usually discussed under several terms, such as psychological maltreatment and emotional maltreatment , which emphasize teachers' verbal aggressive behaviors and the effects of such behaviors on their students ( Fromuth et al., 2015 ; Geiger, 2017 ; Longobardi et al., 2018 ); school corporal punishment , which focuses on physical aggression ( Deb et al., 2017 ; Gershoff, 2017 ); student maltreatment by teachers , which encompasses teachers' physical and emotional aggression ( Lee, 2015 ); and teachers' aggression , which focuses on teachers' verbal aggressive behaviors ( Riley et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%